Karakterisasi Ekstrak Kolagen Ceker Ayam Menggunakan Metode Ekstraksi Microwave dengan Variasi Konsentrasi Asam Asetat - Diana Nur Miftakh (Fakultas Teknologi Pertanian, 2025)
Collagen is the main structural protein found in connective tissue. Collagen has a highly complex tertiary structure and forms a circular coil structure. Collagen can be utilized in the food industry, one of which is functional beverages that are widely consumed. This situation has led to high collagen import values. Therefore, steps have been taken to utilize chicken feet as a collagen source due to their high protein content. Collagen extraction can be performed using the MAE (Microwave Assisted Extraction) method with acetic acid as the solvent. The objective of this study is to determine the physical and chemical characteristics of chicken feet collagen extract using the microwave method with varying acetic acid concentrations, as well as to identify the optimal treatment for collagen extraction from chicken feet using the microwave method with varying acetic acid concentrations based on the characteristics of chicken feet collagen. The research method involved varying the acetic acid concentration at 0.3, 0.5, and 0.7 M with three repetitions. The observed parameters included yield analysis, pH, color, solubility, water holding capacity, oil holding capacity, viscosity, antioxidant activity, effectiveness testing, and collagen functional groups. The results showed that the use of the microwave method with varying acetic acid concentrations affected collagen characteristics such as yield, pH, color, water holding capacity, oil holding capacity, solubility, viscosity, and antioxidant activity. The best treatment was obtained at an acetic acid concentration of 0.7 M with a yield of 5.90%; pH 6.36; brightness 74.56; redness 11.49; yellowness 24.19; whiteness 63.06; solubility 84.05%; water holding capacity of 1.32 g/g; oil holding capacity of 2.50 g/g; viscosity of 1.23 cps; and antioxidant activity of 27.82%. The FTIR spectrum results of chicken feet collagen extract treated with 0.7 M acetic acid showed that the absorption peak of amide A was 3323.41 cm-1 , amide B at a wavenumber of 2924.09 cm-1 , amide I at a wavenumber of 1631.78 cm-1 , amide II at a wavenumber of 1546.91 cm-1 , and amide III at a wavenumber of 1234.44 cm-1 .
Reaploud Repository February 2026_Hasyim
Keywords: Collagen; Chicken Feet; Microwave Assisted Extraction; Acetic Acid